Surface roughness of sputtered silicon. II. Model verification - Ali, Mohammad Yeakub; Hung, NguyenPhu (Taylor and Francis Inc., 2001)
Experimental verification of the mathematical surface roughness model for sputtered silicon was performed. The beam shape and its significant level of intensity were determined first by measuring the topography of craters sputtered by focused ion beam (FIB). Then the beam function was generated for various combinations of beam parameters. The material function was developed both by theoretical and experimental analysis. These two functions were then used in the model to calculate the theoretical surface roughness. Microsurface analysis was formed by FIB sputtering of a (100) silicon wafer. The surface roughness at the bottom of the sputtered features was then measured using an atomic force microscope. The theoretical surface roughness was found to be within ±1 and ±5 nm of the measured surface roughness with the measurement uncertainty (standard deviation) of about ±0.36 and ±0.85 nm for R a and R t, respectively.